Exploring Challenges in Speaking English as A Foreign Language: English - St. Humaera Rusli; novalia tanasy; Ana Rosida (Prodi Tadris Bahasa Inggris, 2024)
This research aims to find and describe the various obstacles and the most dominant hindering factors experienced by students that inhibit their ability to speak English in class. This researcher was conducted at SMA Swasta Islam Terpadu Darul Istiqamah in the 2023-2024 academic year. The sample for this research comprised 11th-grade in the second semester. This research uses mixed methods, utilizing questionnaires and interviews as instruments for data collection. This research explores two main hindering factors: affective factors and linguistic factors. The results indicate that the highest barriers preventing students from speaking in English class are affective factors, such as fear of making mistakes, shyness, and lack of motivation. Meanwhile, in terms of linguistic factors, the only notable obstacle is a lack of fluency. These findings suggest that affective factors are the most dominant barriers affecting students' ability to speak in English class